Desplumado = Featherless - Herrera, Juan Felipe; Cuevas, Ernesto (San Francisco Calif. : Children's Book Press, 2004)
Although Tomasito's spina bifida keeps him in a wheelchair, where he often feels as confined as his flightless and featherless pet bird, he discovers that he can feel free when he is on the soccer field.
Keywords: Mexican Americans -- Fiction; Spina bifida -- Fiction; People with disabilities -- Fiction; Birds as pets -- Fiction; Spanish language materials -- Bilingual; Mexicano-americanos -- Novela juvenil